ANALISIS KARAKTERISTIK DEBIT PADA DAS TUNUO, KECAMATAN TOBELO BARAT KABUPATEN HALMAHERA UTARA - Ronald Kondolembang (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
The flow rate of watershed is in the form of volume flow rate of water through a river cross section per unit time. Data discharge or flow is the most important information for the management of water resources , as given by the community water needs depend on the availability of water in a watershed, especially in the dry season.This study aims to investigate the characteristics of flow in the watershed of Tunuo and it is useful for the planning of sustainable water management. This research was carried out by means of direct measurement of the flow rate in the watershed with the stage as follows: measurements of the river profile and flow rate as well as direct observation of the climate conditions. The analysis used using Debit hydrograph analysis that describes the amount of time required for the discharge is increased in a particular rain event as well as the use of biophysical parameters i.e. watershed topography, soils and land cover conditions .Discharge characteristics based on the analysis of hydrograph explain the rise time discharge after rain event into the peak discharge in the Tunuo watershed takes over 5 hours while the time (base time) is about 16 hours. This is due to the role of biophysical factors of the Tunuo watershed in inhibiting the flow rainwater as dominant topography of watershed (flat and sloping)and also forest vegetation cover and mixed farms is still dominant.